THE DETERMINANT OF AUDITOR’S INTEREST IN USING COMPUTER ASSISTED AUDIT TECHNIQUE TOOLS (CAATT): THE MODIFIED TECHNOLOGY ACCEPTANCE MODEL (TAM) AND THEORY OF PLANNED BEHAVIOR (TPB) - Kartika Sari, Ni Putu Eviana (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to test the influence of perceived usefulness, perceivedease of use, auditor’s attitude, subjective norm, and perceived behavioral control onauditor’s interest in using Computer Assisted Audit Technique Tools (CAATT).The data of this research are obtained from the auditors who work in publicaccounting firm of East Java by using convenience sampling method and thequetionnaires distributed as a survey to gather the data from respondents and as aresult, there are 109 questionnaires or 71.2 percent data out of the number of thequestionnaires that were distributed. Later the data was analyzed using Partial LeastSquare with an application named SmartPLS to test the variables relationship. The results show that auditor’s interest in using CAATT influenced byperceived usefulness and subjective norm. Meanwhile, auditor’s attitude influencedby perceived usefulness and perceived ease of use. In addition, auditor’s interest isnot influenced by auditor’s attitude and perceived behavior control.Key Word: Perceived Usefulness, Perceived Ease of Use, Auditor’s Attitude, Subjective Norm, Perceived Behavior Control, Auditor’s Intention,and CAATT.